The Other Sensory Approach on Exploring Urban Heritage Landscape. Case Study: Chinese Quarter of Semarang - Auliya M Alqadrie; Widjaja Martokusumo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
A new interpretation is needed to give meaning to conservation in the urban development framework and to support a sustainable cultural environment. Based on Québec Declaration (2008) and Burra Charter (2013), intangible dimensions became matter to give a richer and deeper meaning to the cultural heritage area. A shift has been seen in urban theories arguing for attention to the multi-sensory approach. This concept becomes matters as the raising critique towards the domination of visual perception in the built environment's design. The domination of audio-vision starting to reach out by the practitioners and scholars, unlike the other senses such as smell, tended to overlook and misconception. This paper outlines a pilot study's findings addressing holistic person-sensory experience in exploring the role of odor in shaping the cultural heritage area in Pecinan nowadays. It will discuss various scents detected, personal perception, and the link between odor and Pecinan's character. All this data was collected using a smells walk, questionnaire survey, and interview. This research aims to explore the potential interface in preservation conflict between the character of existing historic town and change as smellscape is part of the intangible element and part of triangle components of a sense of place in supporting successful urban place.